Substitution as a consequence of liability arising from breach of the promise of preference: A comparative study - شرقي, عمر مال الله; عبد الرضا, حسين عبدالله (Journal of Legal Sciences, 2021)
The judicial transformation led by the French Court of Cassation about the consequence of liability arising from breach of the promise of preference led to the adoption of a new principle، whereby the beneficiary of the promise of preference would substitute with the third party in the concluded contract in violation of his right in preference. This shift، in turn، has been reflected on the legislative situation in France، where the French legislator adopted this principle in the New Contract Law of 2016.